Does milk matter: Is children's intake affected by the type or amount of milk served at a meal?. (1st October 2016) - Kling, Samantha M.R.; Roe, Liane S.; Sanchez, Christine E.; Rolls, Barbara J.
Abstract: Increasing the energy density (ED) and portion size of foods promotes additional energy intake, but the effect of similar changes in milk is unknown. Using a crossover design, we tested the effect of varying the ED and portion size of milk served with lunch on preschool children's intake. Lunch was served in childcare classrooms on 4 days to 125 children aged 3–5 y (67 boys; 58 girls). Across the meals, milk was varied in ED (lower-ED [1% fat]; higher-ED [3.25% fat]) and portion size (100% [183 g]; 150% [275 g]). Foods in the meal were not varied; children ate as much of the meal as they wanted. Serving higher-ED milk did not affect milk intake by weight, but increased energy intake from milk by 31 ± 2 kcal compared to serving lower-ED milk (P < 0.0001). Serving the 150% portion of milk increased milk intake by 20 ± 3 kcal compared to serving the 100% portion (P < 0.0001). Increases in both ED and portion size combined to increase milk intake by 49 ± 4 kcal (63%; P < 0.0001). Across all children, food intake decreased when higher-ED rather than lower-ED milk was served, but meal energy intake (food + milk) did not change significantly. This response varied by sex: for boys, serving higher-ED milk decreased food intake by 43 ± 8 kcal (P < 0.0001) but did not affect meal energy intake, while for girls, higher-ED milk did not reduce food intake so that meal energy intake increased by 24 ± 10 kcal (P = 0.03). Thus, boys adjusted food intake in response to changes in ED of milk consumed with lunch, but girls did not. Serving milk in larger portions promotes intake of this nutrient-dense beverage, but the effects of milk ED on meal intake vary between children.